Faktor- Faktor Yang Mempengaruhi Kinerja Guru Ekonomi Pada SMA Negeri Di Kota Makassar - Farmawati, Eka; Ramli, Anwar; Rahmatullah, Rahmatullah (Universitas Negeri Makassar, 2018)
The purpose of this study was to determine the number of teachers, principals, work motivation, environment and teacher's welfare on economic performance in public high schools in Makassar City as a whole and simultaneously. Data collection techniques are carried out through questionnaire techniques and documentation. Data analysis techniques are Normality Test, Multiple Linear Regression Analysis, T-Test and F Test. The results showed that partially and simultaneously teacher competency, principal leadership, teacher work motivation, work environment and teacher welfare had a significant and significant effect on the performance of economic teachers in public high schools in Makassar City